Noradrenaline modulates mechanically evoked responses in the rat spinal dorsal horn: an in vivo patch-clamp study - Sonohata, Motoki (J Pain Res, 2019)
Purpose: We investigated the effects of noradrenaline (NA) on physiologically evoked synaptic responses of substantia gelatinosa (SG) neurons using anesthetized animals. Methods: Male Sprague–Dawley rats (6–8 weeks, 200–300 g, n=21) were anesthetized. The lumbar spinal cord was exposed from L3 to L5; subsequently, the rats were fixed to a stereotaxic apparatus. The electrode was advanced at an angle of 30–45 degrees into the SG using a micromanipulator. We recorded excitatory post-synaptic currents (EPSC). Under these conditions, innocuous or noxious mechanical stimuli were applied to the receptive ﬁeld of the ipsilateral hindlimb with or without NA, respectively. Results: NA (50 μM) pre-application induced three types of responses for pinch-evoked EPSCs. The number of neurons showing inhibition, facilitation, and no-effect was 15 (71.4%), 2 (9.5%), and 4 (19%), respectively (n=21). Pre-treatment with NA also induced three different types of responses for puff-evoked EPSC (n=21). The number of neurons showing inhibition, facilitation, and no-effect was 9 (42.9%), 9 (42.9%), and 3 (14.2%), respectively. Further, there was a significant difference in the rate distribution (inhibition, facilitation, and no change) between puff- and pinch-evoked responses. Conclusion: Our present data indicate that NA acts on noxious and innocuous mechanical transmission in the SG. Considering the distinct sensory inputs to the SG, the different actions of NA on the transmission of sensory information imply that NA exerts its analgesic effects in a manner more complicated than previously believed.